Effectiveness of HIV risk reduction interventions among men who have sex with men in China: a systematic review and meta-analysis. - Hongyan Lu; Yu Liu; Kapil Dahiya; Han-Zhu Qian; Wensheng Fan; Li Zhang; Juntao Ma; Yuhua Ruan; Yiming Shao; Sten H Vermund; Lu Yin (PLoS ONE, 2013)
To evaluate the effect of risk reduction interventions on HIV knowledge, attitudes and behaviors among men who have sex with men (MSM) in China.We performed a systematic review and meta-analysis of HIV risk reduction intervention studies among Chinese MSM. The summary difference of standardized mean differences (SMD) between both study arms or between pre- and post-intervention assessments were defined as the effect size (ES); ES was calculated using standard meta-analysis in random effects models.Thirty-four eligible studies were included in the analysis, including two randomized clinical trials (RCT), six quasi-experimental studies, six pre-and-post intervention studies, and twenty serial cross-sectional intervention studies. These studies showed an increase in consistent condom use with any male sexual partners (mean ES, 0.46; 95% confidence interval [CI], 0.35-0.56), with regular sexual partners (mean ES, 0.41; 95% CI, 0.18-0.63), and casual sexual partners (mean ES, 0.52; 95% CI, 0.24-0.79). The analysis of ten studies that measured the impact on uptake of HIV testing also showed a positive result (mean ES, 0.55; 95% CI, 0.38-0.71). The risk reduction interventions also improved HIV/AIDS-related knowledge (mean ES, 0.77; 95% CI, 0.60-0.94) and attitudes (mean ES, 1.35; 95% CI, 0.91-1.79), but did not reduce prevalence of HIV (mean ES, 0.23; 95% CI, 0.02-0.45) and syphilis infections (mean ES, -0.01; 95% CI, -0.19-0.17). There was significant heterogeneity among these studies.On aggregate, HIV risk reduction interventions were effective in reducing risky behaviors and improving knowledge and attitudes among Chinese MSM, but were not associated with a change in the prevalence of HIV and syphilis. Future studies should use incidence as definitive study outcome.